Lean Management and Green Supply Chain Management Implementation on the Manufacturing and Logistics Industry at an Indonesia - Muhammad Andika Firmansyah; Siti Maemunah (Business and Entrepreneurial Review, 2021)
This research is on the manufacturing and logistics industry in Indonesia in improving environmental performance. This study aims to implementation of lean management and green supply chain management to environmental performance. The methodology used in this study is primary data, 150 respondents from logistics professionals. This study uses SEM-PLS. The results showed that lean management had no significant effect on environmental performance. The implications of this study are focused on geography and small samples.  Green supply chain management is oriented towards the environment in making supply chain decisions to improve environmental performance.